The effect of thermal gradients on the performance of battery packs in automotive applications - Marinescu,M; Wu,B; Von,Srbik M; Yufit,V; Offer,GJ (Iet Conference Publications, 2013)
Thermal gradients arising inside a battery pack for automotive applications are calculated for 200 A discharge via a multiparticle thermal-electrochemical coupled high fidelity model for a 12P7S 4.8 Ah cell pack. The effect of such gradients at the cell level are studied in a first approximation under a corresponding discharge at 15 A, by discretising the cell into units at fixed temperatures throughout the discharge. The immediate time evolution of load distribution through the various parts of the cell shows a complex behaviour, dependent on parameters such as temperatures, state of charge and load characteristics.